(untitled) (Italian Journal of Public Health, 2009)
It is very good news for Italian participation at this year’s EUPHA meeting, which will be held in Lodz (Poland). From 25 to 28 November the joint annual conference EUPHA-ASPHER will see a peaceful “invasion” from Italy. Out of the 63 Italian abstracts submitted to the conference organisers, only 5 (7.9%) were rejected. Overall, 11.6% of all of the accepted abstracts are Italian, 9.8% of the oral presentations and 13% of the poster presentations. These results pay testimony to the high quality of European public health research and practice reached in several fields and settings (academic, public health regional agencies, and local health units). Highlights from Italy include the ongoing work in the field of infectious disease control, Stefania Bruno (Catholic University) will present the Roman experience of Tubercolosis surveillance in the homeless. Maria De Giusti (Sapienza University) presents “Knowledge, attitudes and behaviour towards Methicillin-resistant Staphylococcus aureus skin infections and S. aureus nasal colonisation”; while Chiara de Waure (Catholic University) will present “Rapid screening tests for MRSA carriage at hospital admission: a systematic review”.